2018
DOI: 10.1126/science.aat8849
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for preventing asymmetric histone segregation onto replicating DNA strands

Abstract: How parental histone (H3-H4) tetramers, the primary carriers of epigenetic modifications, are transferred onto leading and lagging strands of DNA replication forks for epigenetic inheritance remains elusive. Here we show that parental (H3-H4) tetramers are assembled into nucleosomes onto both leading and lagging strands, with a slight preference for lagging strands. The lagging-strand preference increases markedly in budding yeast cells lacking Dpb3 and Dpb4, two subunits of the leading strand DNA polymerase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
293
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 214 publications
(311 citation statements)
references
References 40 publications
17
293
1
Order By: Relevance
“…In particular, we found that loss-of-function mutations in the genes coding for the POLE3/POLE4 histone-fold complex causes ATRi hypersensitivity in human cells. POLE3 and POLE4 form an ancillary subunit complex of DNA polymerase e involved in histone deposition at the replication fork (Bellelli et al 2018a;Yu et al 2018). Our results using a POLE3 separation-of-function mutant suggest, however, that impaired histone deposition does not underlie the observed ATRi sensitivity pointing rather to its function in DNA synthesis.…”
Section: Introductionmentioning
confidence: 65%
“…In particular, we found that loss-of-function mutations in the genes coding for the POLE3/POLE4 histone-fold complex causes ATRi hypersensitivity in human cells. POLE3 and POLE4 form an ancillary subunit complex of DNA polymerase e involved in histone deposition at the replication fork (Bellelli et al 2018a;Yu et al 2018). Our results using a POLE3 separation-of-function mutant suggest, however, that impaired histone deposition does not underlie the observed ATRi sensitivity pointing rather to its function in DNA synthesis.…”
Section: Introductionmentioning
confidence: 65%
“…Recent reports demonstrate conserved roles of two replisome components, Dpb3 and Mcm2, in producing a more symmetric distribution of parental H3-H4 tetramers between the leading and lagging strands. Specifically, dpb3∆ causes biased parental H3-H4 tetramer inheritance to the lagging strand (Yu et al 2018) and a set of point mutations in MCM2 (mcm2-3A) causes biased parental H3-H4 tetramer inheritance to the leading strand (Petryk et al 2018;Gan et al 2018).…”
Section: Replisome Defects Affected Epigenetic Inheritancementioning
confidence: 99%
“…Though the rate of silencing loss increased in replisome mutant backgrounds, the large majority of silenced cells still faithfully transmitted the silenced state through cell divisions. Indeed, though dpb3∆ and mcm2-3A single mutants exhibit asymmetric parental H3-H4 tetramer inheritance (Yu et al 2018;Petryk et al 2018), it is likely that this asymmetry is not complete and some parental H3-H4 tetramers are still stochastically transmitted to each daughter chromatid during DNA replication.…”
Section: Variations In Nucleosome Number In Replisome Mutant Backgroundsmentioning
confidence: 99%
See 2 more Smart Citations